Pull Strategy and Digital Marketing Optimization for House of Garment MSMEs as Brand Identity Enhancement by Legality Management, Company Profile and Website Making - Ihsanul Afwan; Rambat Lupiyoadi (Green Publisher Indonesia, 2023)
The Covid-19 pandemic has hit various sectors including the textile industry, where raw material prices have experienced a significant spike amidst a decline in demand. One of the affected companies is Malabis, a garment house that was established in 2015 in South Tangerang. The company's B2B business model makes their brand known only by word of mouth and grows organically according to the word of mouth concept. When the pandemic started to subside, the company had to adapt from the beginning because the brand identity was relatively shabby. Implementing a pull strategy and digital marketing through social media channels such as websites, creating company profiles, and managing business legality will be a way to improve Malabis' brand identity to optimize sales. The aim of this study is enhancing brand identity to improve sales. The study will be followed through using a qualitative approach with descriptive analysis using data collection models such as in-depth interviews, observation or direct observation, and literature review based on data, facts, and findings in the field. Another thing that will certainly be carried out is starting from reviewing business model canvas, SWOT, Five Forces Model, VRIO Framework, GAP Analysis, and Pareto contributions to get the best solution to the problems being faced and trying to be solved. The research resulting in uplift in the turnover average (41.6%) compared to the previous year. Malabis MSMEs’ overall brand identity has been improved through optimizing the pull strategy and digitak marketing through Instagram channel and Website Creation